Long-term effects of phacoemulsification surgery on intraocular pressure in patients with primary open-angle glaucoma and pseudoexfoliation glaucoma - Ozturk, Emrah; Gul Firat, Penpe (Annals of Medical Research, 2021)
Aim: To compare the long-term effects of phacoemulsification surgery on intraocular pressure (IOP) in primary open-angle glaucoma (POAG) and pseudoexfoliation glaucoma (PXG) patients.Material and Methods: This is a retrospective-comparative study. The data of the patients who underwent phacoemulsification surgery by the same surgeon between 2010 and 2016 and followed up more than 24 months postoperatively were collected. While group 1 consisted of 24 patients with POAG group 2 consisted of 16 patients with PXG. Preoperative, postoperative 1st day, 1st, 12th, 18th, 24th, 36th and 48th months IOP and best corrected visual acuity (BCVA) were enrolled. Results: The mean follow-up time of group 1 was 44.17 ± 17.8 months and 43.13 ± 19.4 months for group 2 (p= 0.86). There was no statistically significant difference between the groups in the preoperative, postoperative 1st day, 1st, 12th, 18th, 36th and 48th months IOP (p>0.05). There was a statistically significant difference for the IOP value measured postoperative 24th month between the groups (p= 0.005). There was a statistically significant difference between preoperative and postoperative 1st, 12nd months IOP measurements in group 1 (p= 0.02; p= 0.009, respectively). There was a statistically significant difference between preoperative and postoperative 24th months IOP measurements in group 2 (p=0.01). Conclusion: Although phacoemulsification surgery may cause an increase (14-19 %) in IOP early postoperative period in eyes with POAG and PXG, may provide a modest level decreases (19-18 %) in the long term.
Keywords: Cataract; Intraocular pressure; Phacoemulsification; Primary open-angle glaucoma; Pseudoexfoliation glaucoma